Girl Performances in EFL Learning in Benin: A Case Study of LMJF of Natitingou in the Region of Atacora - KOTTIN, Assogba Evariste (My University, 2023)
Women and girls are expected to ensure their personal commitment, a pledge that goes through the principles of both equity and equality for women in all fields. Whenever EFL teachers develop strategies to enhance learners’ performances, girls and young women are to engage in decision-making processes. The fundamental objective of the current study is to examine and make an analytical comparison of the English learners’ performances of LMJF Natitingou in Benin. In addition to the moderate use of the Internet, I have addressed questionnaire to 88 students, 85 collected, the sample size is 70; 27 EFL teachers, 23 collected, the sample size is 22; and interviews conducted with 6 among them without forgetting the 2 inspectors (8 in total), the sample size is 8, through phone calls, Whatsapp, Facebook, Email, and face to face. The results obtained have been analyzed and transcribed. These results reveal that girls’ performances are globally lower than boys’ in Beninese secondary schools; however the case of LMJF of Natitingou is commendable and is worth imitating for the development of Beninese educational system. My suggestions towards young girls are mainly that they should be proud of themselves with no inferiority complex and fatal exploitation from men and boys so as to show female higher degree of wisdom.
Keywords: Performances; Girls; EFL Learning; Personal Commitment; Equity; Equality